2016
DOI: 10.1080/15384047.2016.1219819
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing ovarian cancer cells to chemotherapy by interfering with pathways that are involved in the formation of cancer stem cells

Abstract: Chemotherapy often fails to eradicate cancer stem cells (CSCs) that drive cancer recurrence. In fact, the treated tumors often contain a higher frequency of chemo-resistant CSCs. It is thought that CSC formation is supported by exposure of cancer cells to sub-cytotoxic chemotherapy doses as a result of poor drug penetration in epithelial tumors. We have shown that low-dos cisplatin triggers the transdifferentiation of ovarian cancer cells into CSCs through processes that are also involved in the generation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…All three cell lines were 100% positive for DSG2 as measured by flow cytometry (Figure 5(a)). In previous studies 33 and additional preliminary studies, we determined that a concentration of 2.5 µM cisplatin did not decrease the viability of ovc316 and OVCAR5-RFP by more than 10%. In contrast, this dose killed 95% of OVCAR3 cells by day 6, demonstrating the cytostatic effect of the chemotherapy drug.…”
Section: Dsg2 Levels Increase In Tumor Cells Treated With Chemotherapymentioning
confidence: 91%
See 1 more Smart Citation
“…All three cell lines were 100% positive for DSG2 as measured by flow cytometry (Figure 5(a)). In previous studies 33 and additional preliminary studies, we determined that a concentration of 2.5 µM cisplatin did not decrease the viability of ovc316 and OVCAR5-RFP by more than 10%. In contrast, this dose killed 95% of OVCAR3 cells by day 6, demonstrating the cytostatic effect of the chemotherapy drug.…”
Section: Dsg2 Levels Increase In Tumor Cells Treated With Chemotherapymentioning
confidence: 91%
“…Metastatic tissue showed similar expression patterns toward the periphery of the lesion with relatively more uniform distribution throughout the core of the tumor (Figure 1(b)). Immunofluorescent staining of a xenograft tumor derived from a primary ovarian cancer cell line, ovc316, 33,34 showed abundant levels of DSG2 at the edges of the tissue co-localizing with claudin-7, another key junction protein (Figure 1(c), S3). This indicated that ovarian cancer tissue of primary, metastatic, and cell line origins have predominant membrane-localized DSG2, whereby it is not exclusively trapped in junctions and accessible to potential ligands.…”
Section: Dsg2 Is Overexpressed In Ovarian Cancer Primary and Metastatmentioning
confidence: 99%
“…Studies attempting to exploit similarities between CSCs and iPSCs to sensitize cancers to conventional therapies have been attempted. 85 Using Nanog as a reporter of CSC formation, Saydaminova and colleagues identified the compound GDM-1515 to be a regulator of histone demethylases that is capable of sensitizing CSCs to cisplatin-induced apoptosis. 85 This compound was able to inhibit epithelial-mesenchymal transition (EMT) and induction of CSCs by cisplatin.…”
Section: Sensitizing Cscs To Chemotherapymentioning
confidence: 99%
“…85 Using Nanog as a reporter of CSC formation, Saydaminova and colleagues identified the compound GDM-1515 to be a regulator of histone demethylases that is capable of sensitizing CSCs to cisplatin-induced apoptosis. 85 This compound was able to inhibit epithelial-mesenchymal transition (EMT) and induction of CSCs by cisplatin. On the other hand, an unbiased screen for small molecules cytotoxic to CSCs revealed salinomycin, a natural compound that can reduce expression of CSC genes and mammary tumor growth and increase epithelial differentiation of mammary gland tumors.…”
Section: Sensitizing Cscs To Chemotherapymentioning
confidence: 99%
“…Other CSC-related signaling pathways more commonly studied, not reviewed here, but relevant to stemness include MYB, TGF-β, JAK-STAT, FGFs, PI3K, or MEK. Targeting these pathways has been shown to exert anti-CSC effects, and promising agents are currently under investigation, as recently reviewed elsewhere ( 30 , 36 , 37 , 47 , 48 , 51 , 62 , 64 74 ).…”
Section: Introductionmentioning
confidence: 99%